Isomerization of an enzyme-coenzyme complex in yeast alcohol dehydrogenase-catalyzed reactions - DRAGINJA PERICIN (Journal of the Serbian Chemical Society, 2003)
In this work, all the rate constants in the kinetic mechanism of the yeast alcohol dehydrogenase-catalyzed oxidation of ethanol by NAD+, at pH 7.0, 25°C, have been estimated. The determination of the individual rate constants was achieved by fitting the reaction progress curves to the experimental data, using the procedures of the FITSIM and KINSIM software package of Carl Frieden. This work is the first report in the literature showing the internal equilibrium constants for the isomerization of the enzyme-NAD+ complex in yeast alcohol dehydrogenase-catalyzed reactions.